A comprehensive review on advances in TiO2 nanotube (TNT)-based photocatalytic CO2 reduction to value-added products - Hossen, Md. Arif; Solayman, H. M.; Leong, Kah Hon; Sim, Lan Ching; Yaacof, Nurashikin; Abd Aziz, Azrina; Lihua, Wu; Monir, Minhaj Uddin (MDPI AG, 2022)
The photocatalytic reduction of CO2 into solar fuels by using semiconductor photocatalysts is one of the most promising approaches in terms of pollution control as well as renewable energy sources. One of the crucial challenges for the 21st century is the development of potential photocatalysts and techniques to improve CO2 photoreduction efficiency. TiO2 nanotubes (TNTs) have recently attracted a great deal of research attention for their potential to convert CO2 into useful compounds. Researchers are concentrating more on CO2 reduction due to the rising trend in CO2 emissions and are striving to improve the rate of CO2 photoreduction by modifying TNTs with the appropriate configuration. In order to portray the potential applications of TNTs, it is imperative to critically evaluate recent developments in synthesis and modification methodologies and their capability to transform CO2 into value-added chemicals. The current review provides an insightful understanding of TNT production methods, surface modification strategies used to enhance CO2 photoreduction, and major findings from previous research, thereby revealing research gaps and upcoming challenges. Stability, reusability, and the improved performance of TNT photocatalysts under visible light as well as the selection of optimized modification methods are the identified barriers for CO2 photoreduction into valuable products. Higher rates of efficacy and product yield can be attained by synthesizing suitable photocatalysts with addressing the limitations of TNTs and designing an optimized photoreactor in terms of the proper utilization of photocatalysts, incident lights, and the partial pressure of reactants.